Commutation to zero voltage and zero current of a three-phase AC-AD converter that uses a single controlled stage of potency processing - Vargas, Pedro; Contreras, José (Rev. Téc. Fac. Ing. Univ. Zulia)
In this paper, analysis of a Zero Voltage-Current Switching (ZVCS) with a single stage of power processing converter is presented. A drive strategy for the activation of Full Bridge (FB) inverter using Phase Shift (FS) pulse width modulation (PWM), is describe in order to achieve ZVS in a leading leg and adjustment of the output DC voltage. A simple auxiliary circuit is used to achieve ZCS in a lagging leg. A mathematical and graphic analysis is made in order to obtain a approach to adjust the die time of a leading leg and the selection of the components of the auxiliary circuit. Experimental results are included for a 1.5kW, 50kHz and 60V output three phase AC-DC converter which confirms the performance of de proposed topology.